2015
DOI: 10.1080/13607863.2014.1003288
|View full text |Cite
|
Sign up to set email alerts
|

The interpersonal needs questionnaire with a shortened response scale for oral administration with older adults

Abstract: Objectives The purpose of this paper is to examine the psychometric properties and construct validity of the Interpersonal Needs Questionnaire (INQ) using a modified 3-point response scale for oral administration with older adults. Methods In-home interviews were conducted with 269 participants aged 60 and older who were completing an eligibility interview for a randomized control trial. The INQ was administered orally, as were measures of social support, death and suicide ideation and meaning in life. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The SNI was developed by the study authors based on items selected from a series of previously validated measures of the component dimensions. These measures included the Hewett‐Flett Perfectionism Scale (Hewitt, Flett, Turnbull‐Donovan, & Mikail, ), the Goal Adjustment Scale (Wrosch, Scheier, Miller, Schulz, & Carver, ), the Interpersonal Needs Questionnaire (Parkhurst, Conwell, & Van Orden, ), the Perceived Criticism Scale (Hooley & Teasdale, ), the Humiliation Inventory (Hartling & Luchetta, ), and the Defeat Scale/Entrapment Scale (Griffiths et al., ). Select items were taken from each instrument and reformatted into a 5‐point Likert scale from not at all true to extremely true .…”
Section: Methodsmentioning
confidence: 99%
“…The SNI was developed by the study authors based on items selected from a series of previously validated measures of the component dimensions. These measures included the Hewett‐Flett Perfectionism Scale (Hewitt, Flett, Turnbull‐Donovan, & Mikail, ), the Goal Adjustment Scale (Wrosch, Scheier, Miller, Schulz, & Carver, ), the Interpersonal Needs Questionnaire (Parkhurst, Conwell, & Van Orden, ), the Perceived Criticism Scale (Hooley & Teasdale, ), the Humiliation Inventory (Hartling & Luchetta, ), and the Defeat Scale/Entrapment Scale (Griffiths et al., ). Select items were taken from each instrument and reformatted into a 5‐point Likert scale from not at all true to extremely true .…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative studies addressing protective factors have shown that strong reasons for living are associated with adaptive coping skills (i.e., problem-focused and emotion-focused coping)(Marty, Segal, & Coolidge, 2010) and a sense of belonging (McLaren, Gomez, Bailey, & Van Der Horst, 2007). Further, higher meaning in life (Heisel, et al, 2006) and higher social support (Parkhurst, Conwell, & Van Orden, 2015) demonstrate negative associations with suicide ideation in older adults, indicating they may serve as protective factors. Spirituality has also been shown to buffer the association between loss of meaning in life and depression among older adults (Bamonti, Lombardi, Duberstein, King, & Van Orden, 2015).…”
Section: The Voice Of the Older Personmentioning
confidence: 99%
“…The theory also posits distinct pathways by which suicidal desire and both nonfatal and fatal suicidal behaviors develop. In this regard, the interpersonal theory is the first theory of suicide positioned within what would later be termed the ideation-to-action framework (Klonsky & May, 2014; Klonsky et al, 2016; Nock et al, 2016). …”
Section: Introductionmentioning
confidence: 99%